Profil perlemakan darah ayam broiler yang diberi pakan tepung daun kayambang (Salvinia molesta) - Destriana Meliandasari; Bambang Dwiloka; Edjeng Suprijatna (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2014)
The aim of this study was to determine the effect of alternative local feed ingredients kayambang leaf meal (Salvinia molesta) as a fibrous protein source in broiler diet composition on the production performance and blood lipid. The study used one hundred broiler chickens at 15 days old unsex with average weight 500 ± 6,99 g. The study used experimental completely randomized design with four treatments and five replications. Ration treatment was arranged for starter and finisher periods including T0 (ration without Salvinia molesta leaf meal); T1 (ration with 6% of Salvinia molesta leaf meal); T2 (ration with 12% of Salvinia molesta leaf meal); and T3 (ration with 18% Salvinia molesta leaf meal). The results showed that Salvinia molesta leaf meal treatment in broiler diet significantly (P <0.05) influenced  body weight gain, feed conversion, and blood lipid. However, the treatment had no significant effect (P>0.05) on feed consumption and carcass percentage. The conclusion of the study was the use of Salvinia molesta leaf meal decreased the production performance of broiler chickens. In addition, the use of Salvinia molesta leaf meal in broiler rations increased blood lipid profiles although they were still within the normal limits.   Keywords: Salvinia molesta, ration, performance, lipid, broiler